Formation of Students' Religious Character Through the Habit of Dhuha dnd Tahfid Prayers Al-Qur'an (Case Study of Mts Nurussalam Jatiwaras Tasikmalaya Regency) - Amir Diki Fauzi Rahman; Neneng Mutmainah; Imam Naufal Ataqi; Vina Septiana; Dede Aji Mardani (al-Afkar, Journal For Islamic Studies, 2024)
The aim of this research is to find out the problems that occur in the formation of religious character through the habit of praying the midday prayer and Tahfidz Al-Quran. The analytical method used in this research is the qualitative descriptive analysis method. The data collection techniques used in this research are observation, interviews and documentation methods. The results of the research show that there are several problems that occur, including first, a lack of discipline and student interest, second, a lack of coordination of implementers in the field, third, there are no strict regulations regarding the sanctions that will be received for not following. Improvement efforts that can be taken are as follows: first, increasing student discipline by making regulations regarding rewards and punishment, second, it is necessary to create a work program that regulates implementers in the field. Third, there must be concrete regulations made by the Institution so that there are written regulations that serve as a reference for implementation in the field.